Associations between serum pigment epithelium-derived factor and physical performance in older women: The Otassha study - Hiromichi Tsushima; Takashi Shida; Sho Hatanaka; Takahisa Ohta; Narumi Kojima; Hiroyuki Sasai; Masataka Sugimoto (PLoS ONE, 2025)
Pigment epithelium-derived factor (PEDF) contributes to the beneficial effects of exercise by suppressing cellular senescence in multiple organs. Its expression declines in the skeletal muscle of aged animals, suggesting a role in age-related frailty. To investigate the association between circulating PEDF and physical performance, we analyzed its associations with skeletal muscle mass and mobility in a cohort of older women. A cross-sectional analysis was conducted in 143 community-dwelling females (mean age 77.01 ± 4.16 years). Serum PEDF and body composition were measured, and physical performance was assessed via gait speed, handgrip strength, leg extension strength, and the Five Times Sit-to-Stand test. Serum PEDF levels positively correlated with skeletal muscle mass index (SMI) and gait speed, while no significant correlation was observed between serum PEDF levels and other physical function parameters. These findings suggest that circulating PEDF is associated with skeletal muscle mass and mobility in older adults, warranting further investigation into its potential role as a myokine in humans.